2018
DOI: 10.7249/rr2490
|View full text |Cite
|
Sign up to set email alerts
|

How Can Neighborhood Parks Be Used to Increase Physical Activity?

Abstract: Parks play an important role in providing venues for physical activity in urban areas but tend to be underutilized, especially for moderate to vigorous physical activity.• Research underscores the need to target efforts to increase park-based physical activity to specific populations.• There are numerous differences in how parks are used among different racial and ethnic groups, different genders, and different age groups.• Park facilities by themselves are not sufficient to attract users; many sit unused or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…This finding is consistent with our earlier study in Garden Grove's Eastgate Park, where users had 40% higher odds of more vigorous activity after the installation of OEE [12]. The new data are also consistent with numerous prior studies of the role of public parks in promoting physical activity for different subpopulations [32][33][34]. Our results advance the state of increasing evidence that OEE is positively correlated with increased activity levels in parks, through data suggesting that this influence occurs regardless of whether the equipment is placed in a specific area of the park or spread throughout the park along a walking path.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with our earlier study in Garden Grove's Eastgate Park, where users had 40% higher odds of more vigorous activity after the installation of OEE [12]. The new data are also consistent with numerous prior studies of the role of public parks in promoting physical activity for different subpopulations [32][33][34]. Our results advance the state of increasing evidence that OEE is positively correlated with increased activity levels in parks, through data suggesting that this influence occurs regardless of whether the equipment is placed in a specific area of the park or spread throughout the park along a walking path.…”
Section: Discussionsupporting
confidence: 92%
“…In this Chinese sample, the findings demonstrate behavior mapping is a promising tool to measure park-based physical activity. As this study associated the levels of use with the landscape features, the results are expected to be useful in design practice for promoting regular physical activity.Numerous studies have shown neighborhood parks provide ideal places for physical activity [19], emphasizing that the presence of or access to nearby nature can contribute to mental and physical health [20][21][22][23][24][25]. Compared with the large number of studies examining the influence of neighborhood-built environment on park usage [26,27], especially the proximity to a park and the surrounding communities [28][29][30], few studies have focused on the specific design features that may influence the park use and the occurrence of physical activity [31].Evidence shows that park attributes are related to park usage, that is, a large size, the quality of facilities, organized activities, and good maintenance can promote overall park use [31][32][33].…”
mentioning
confidence: 99%
“…Numerous studies have shown neighborhood parks provide ideal places for physical activity [19], emphasizing that the presence of or access to nearby nature can contribute to mental and physical health [20][21][22][23][24][25]. Compared with the large number of studies examining the influence of neighborhood-built environment on park usage [26,27], especially the proximity to a park and the surrounding communities [28][29][30], few studies have focused on the specific design features that may influence the park use and the occurrence of physical activity [31].…”
mentioning
confidence: 99%
“…Even though there is only a little difference between men and women in the frequency of visiting neighborhood parks, the younger respondents (those aged 40 and below) of both sexes appear to visit neighborhood parks regularly than older people (those aged above 40). However, Cohen and Leuschner (2018) stated that kids and teens, boys and neighborhoods with low-poverty areas use the neighborhood park the most (see Table 2).…”
Section: Resultsmentioning
confidence: 99%